COMPETITIVE INTELLIGENCE AND ORGANIZATIONAL EFFECTIVENESS IN TELECOMMUNICATION INDUSTRY IN SOUTH-SOUTH, NIGERIA - Maxwell Nwinye (Scholars Digest Publishing, 2025)
This study examined competitive intelligence and organizational effectiveness in telecommunication industry in South South, Nigeria. The researcher adopted survey design. Population of the study contained 160 selected employees from six nominated telecommunication industry in South South, Nigeria. Random sampling method was useful for the purpose of minimizing research errors. The primary data was collected from structured questionnaire whereas the secondary data was information received from company reports and human resource data of various selected telecommunication industry. Taro Yamane’s formula was utilized to get a sample size of 114 employees for the study. Copies of questionnaire were distributed to collect data necessary in answering research questions. Spearman correlation coefficient was used to test the hypotheses. The findings of the study stated that there was a positive significant relationship between competitor intelligence and organizational effectiveness, together with the relationship between technology intelligence and organizational effectiveness was statistically significant. It was concluded that the competitive intelligence predicted organizational effectiveness. researcher recommended that telecommunication industry should promote technology intelligence by applying modern technology to reduce the consistent network failures in Nigeria, in order to achieve organizational effectiveness.
Keywords: Competitive intelligence, competitor intelligence, organizational effectiveness.